The social psychology of power - Guinote, Ana, 1963-; Vescio, Theresa K. (Guilford Press, 2010)
Addressing an issue of central concern in social life, this authoritative book examines how having or lacking power influences the way individuals and groups think, feel, and act. Leading international experts comprehensively review classic and contemporary research with an eye toward bridging gaps across theories and levels of analysis. Compelling topics include the evolutionary bases of power; its effects on physiological processes, cognitive abilities, and health; what sorts of people are given power; when, how, and whom power corrupts; and power dynamics in gender, social class, and ethnic.